Effect of Kaolin Grain Size on Its Efficiency as Anti-Seepage in the Petroleum Industry - Al-Bidry, Mayssaa. Ali; Hamied, Ramzy. S. (Iraqi Journal of Science, 2025)
The study goals encompassed the evaluation of the effectiveness of kaolin liners in preventing the seepage of crude oil with different viscosities. The research used light and heavy crude oils sourced from Al-Barjisiah and Al-Ahdab oil fields in Iraq with kaolin grains of varying sizes. In the first stage, kaolin was analyzed using X-ray diffraction and X-ray fluorescence to identify minerals and chemical composition. The physical characteristics of crude oil were also examined. Ten liners were prepared for the test depending on kaolin grain size ranging from 300, 150, 75, 50 µm and nano size with chosen crude oil. The findings indicated that kaolin liners of various sizes could not retain light crude oil. The flow of heavy crude oil was observed to be impeded, and seepage was effectively stopped for different durations when kaolin liners of varying sizes, precisely 50 µm, 75 µm, 150 µm, and 300 µm, were employed. These durations were measured to be 54, 96, 90, and 72 hours, respectively. Partial replacement of kaolin 150 µm by nano-size kaolin improved liner ability to impede the flow of light and heavy crude oil with a long period of retention time and without seepage.